Morphological and molecular evidence reveals a new species of Laetmogone (Holothuroidea, Elasipodida) from abyssal depths of the south Pacific Ocean - Yun-Lu Xiao; Hai-Bin Zhang (Zoosystematics and Evolution)
A new elasipodid species of holothuroid, Laetmogone multiradiolus sp. nov., was discovered from the abyssal plain adjacent to the Kermadec Trench in the South Pacific Ocean at a depth of 5735 m, representing the deepest record of a Laetmogone species. We provide a detailed description of the morphological features of this newly-discovered species and present molecular data for the new species and two congeneric specimens collected from the South China Sea used in the phylogenetic analyses of the family Laetmogonidae. Furthermore, we provide a taxonomic key to Laetmogone species and discuss the geographical distribution and species diversity for the family Laetmogonidae. More specimens from broader geographical locations and additional molecular data are needed to better investigate the phylogeny, morphology and biogeography of laetmogonid holothuroids.